The process of gas formation in the dough with oat bran and phospholipids - Shevchenko, Anastasiia; Drobot, Vira (My University, 2021)
The effect of oat bran on the gas-forming ability of the dough with lecithin was determined. Samples of dough from high-grade flour with lecithin (3% by weight of flour) and samples with the addition of oat bran in the amount of 5, 7, 10, 15% to replace wheat flour were prepared. Lecithin helps to improve the fertility of yeast due to its plasticization and the presence of choline, which has a positive effect on the condition of yeast cells. But it is reduction of gas formation with oat bran, which will further affect the quality of finished products.
Keywords: oat bran; phospholipids; bakery product; lecithin; кафедра технології хлібопекарських і кондитерських виробів; вівсяні висівки; хлібобулочні вироби; фосфоліпіди; лецитин